THE INFLUENCE OF INSTRUCTIONAL LEADERSHIP, JOB PERFORMANCE, AND COMPENSATION ON ELEMENTARY SCHOOL TEACHERS' WORK MOTIVATION - Muzakkir; Fahmi Hanifa; Zulfadmi (el-Nizami : Jurnal Manajemen Pendidikan, 2025)
The purpose of the study was to analyze the influence of instructional leadership, job performance, and compensation on the work motivation of public elementary school teachers in Temanggung District. This study used a quantitative approach with a survey method. The research sample consisted of 148 teachers selected using proportional random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression after going through the classical assumption test. The results showed that instructional leadership has a positive and significant influence on teacher work motivation with a t value of 5.353 and an effective contribution of 16.4%. Job performance also has a positive effect on teacher work motivation with a t value of 8.076 and an effective contribution of 30.9%. Compensation is the most dominant factor in increasing teacher work motivation with a t-value of 14.711 and an effective contribution of 59.7%. Simultaneously, the three variables contributed 66.7% to teachers' work motivation, while 33.3% was influenced by other factors. This study confirms the importance of effective instructional leadership, high job performance, and fair compensation in improving teachers' work motivation. Therefore, recommendations are given to education policy makers to pay attention to these three factors to improve teacher performance.